PENGARUH KOMBINASI PUPUK N, P, K DAN VERMIKOMPOS TERHADAP KANDUNGAN C-ORGANIK, N TOTAL, C/N DAN HASIL KEDELAI (Glycine max (L.) Merill) KULTIVAR EDAMAME PADA INCEPTISOLS JATINANGOR - Karina Astari; Anni Yuniarti; Emma Trinurani Sofyan (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2016)
Inceptisols is the type of soil in Indonesia that has low fertility. It is necessary to improve the soil fertility through the use of fertilizers and organic matter to raise the quality of Inceptisols. The research was aimed to know the effect of vermicompost and N, P, K fertilizer combination to Organic-C, Total N, C/N and yield of Edamame soybean on Inceptisols at Jatinangor. The research was carried out from March until June 2016 at Ciparanje Experimental Farm, Faculty of Agriculture of University of Padjadjaran at Jatinangor, Sumedang at an altitude about ± 765 meters above sea level. The research used the Randomized Completely Block Design (RCBD) that consisted of eight treatments and three replications. The treatments were: control (no treatment), ½, 1, and 1½ dose recommendation of N, P, K fertilizer (Urea 100 kg ha-1 + SP-36 150 kg ha-1 + KCl 125 kg ha-1), also, 5 and 10 t ha-1 vermicompost. The results showed that combination treatment of vermicompost and N, P, K fertilizer significantly increased Organic-C, Total N, C/N and yeild of Edamame soybean. The combination of 1 dose recommendation of N, P, K fertilizer and 5 t ha-1 vermicompost gave the best result that produced 116,5 g plant ha-1(10,4 t ha-1) yield of Edamame soybean.Keywords: C/N, Edamame soybean, Inceptisols, N,P,K fertilizer, Vermicompost.